Strategy to Create Market-Oriented Business Opportunities, Innovation, and Products to Improve Marketing Performance in the Tourism Industry in South Sulawesi - Remmang, Hasanuddin; Hasanuddin, Arnas; Hasanuddin, Ahmad Anzhari; Hasanuddin, Askari; Amelia, Auditya (Jurnal Ekonomi, 2024)
This research has analyzed the effect of market orientation, innovation and product orientation toward competitive advantage to increase marketing performance. This riset formula is how to create competitive advantage to increase marketing performance. Population which has selected in this research is small and medium scale clothing industry at Semarang. Those are 137 industries. Total sample in this research are 67 industries. Collecting data used questioner, with score start from 1 (very disagree) to 10 (really agree). Analyzed data tool which has been used is SEM (Structural Equation Model) through AMOS program 6.0. The result of data analyze showed that research model can be accepted with goodness of fit, they are chi – square = 234,552; probability = 0,058; GFI = 0,873; AGFI = 0,84; TLI = 0,985; CFI = 0,987; CMIN/DF = 1,61; and RMSEA = 0,033. All hypothesis can be accepted after SEM analyzes conducted. This matter means market orientation, innovation and entrepreneurship orientation have positive affect and significant toward competitive advantage. Then competitive advantage has positive affect and significant toward marketing performance. General conclusion from result of the model test which has applied to small and medium scale clothing industry at Semarang showed that competitive advantage can be reached through market orientation, innovation and entrepreneurship orientation, from there competitive advantage which has been produced by the industry can increase marketing performance. This research has given some research limitation and also give agenda for the next research.